XY FEMALES DO BETTER THAN THE XX IN THE AFRICAN PYGMY MOUSE, MUS MINUTOIDES. (28th March 2014) - Saunders, Paul A.; Perez, Julie; Rahmoun, Massilva; Ronce, Ophélie; Crochet, Pierre‐André; Veyrunes, Frédéric
<x xml:space="preserve">Abstract</x> All therian mammals have a similar XY/XX sex‐determination system except for a dozen species. The African pygmy mouse, Mus minutoides, harbors an unconventional system in which all males are XY, and there are three types of females: the usual XX but also XX* and X*Y ones (the asterisk designates a sex‐reversal mutation on the X chromosome). The long‐term evolution of such a system is a paradox, because X*Y females are expected to face high reproductive costs (e.g., meiotic disruption and loss of unviable YY embryos), which should prevent invasion and maintenance of a sex‐reversal mutation. Hence, mechanisms for compensating for the costs could have evolved in M. minutoides. Data gathered from our laboratory colony revealed that X*Y females do compensate and even show enhanced reproductive performance in comparison to the XX and XX*; they produce significantly more offspring due to (i) a higher probability of breeding, (ii) an earlier first litter, and (iii) a larger litter size, linked to (iv) a greater ovulation rate. These findings confirm that rare conditions are needed for an atypical sex‐determination mechanism to evolve in mammals, and provide valuable insight into understanding modifications of systems with highly heteromorphic sex chromosomes.